A PERSONALITY ANALYSIS OF THE MAIN CHARACTER IN THE “3 IDIOTS” MOVIE - Yunita, Fhonie Yulma; Siahaan, Safnidar (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
The research described personality of 3 idiots movie directed by Rajkumar Hirani and written by Abhijat Joshi,. The purpose of this research was to analyze the personality development benefits of the main character such as self-confidence, credibility, leadership qualities, interpersonal skills, curiosity, and communication skills, also to find the dominant data of the main character’s personality. In the writing of this research, the researcher used qualitative research method. The researcher used the theory of Donnellan Robins to analyze the personality development benefits. The researcher collected the data from 3 Idiots movie as a primary data. Then for the secondary data sources from books, internet, journal, that is relevance to strengthen the argument. The data collection in this research was done by watching movie and took notes before did the analysis from dialogue, situation that delivered in the movie which becomes the main data of this research. In result of this research, the researcher found that the main character, Rancho, depicted has a high self-confidence.